Health behavior and its relationship to existential anxiety among a sample of health sector students During the Corona pandemic - Alharthi, Sarah Maflh Shaleh (Journal of Educational and Psychological Sciences, 2023)
This study aimed to investigate the relationship between health behavior and existential anxiety among students of health colleges during the Corona pandemic. Tools: The health behavior scale (prepared by the researcher) and the existential anxiety scale prepared by (Saad et al. 2019) were used, and the results of the study concluded that "there is a relationship between health behavior and existential anxiety among the female students in the study sample, as it was found that there are statistically significant differences in the average scores of The sample is on the scale of health behavior and the scale of existential anxiety, as it was found that there is a positive relative contribution of health behavior to the existential anxiety of the female students of the study sample. Nursing, and holding training courses for students of the College of Nursing to reduce their existential anxiety.
Keywords: Health Behavior; Existential Anxiety; Students of Health Colleges